The Influence Of Organization Culture And Commitment Mediated By Motivation To Career Development Of School Administrative Staff In The South Tangerang Regional - Hery Winoto Tj (Publisher Cv. Inara, 2021)
One form of organizational responsibility is in terms of advancing and developing the career of its employees. In educational institutions such as schools, the administrative staff is tasked with maintaining the academic administrative process so that the academic process can run smoothly. This is inseparable from the quality of human resources possessed by schools that have good quality, motivation, and commitment to the institution where they work. Employee career development is one form of rights that quality employees have, this aspect is important because it can provide opportunities for employees and support their welfare.This study aimed to determine organizational culture and commitment mediated by motivation for school administration staff's career development in the South Tangerang Region. Using the purposive sampling technique in this study's data collection, the respondents were administrative staff from schools in the South Tangerang region with 100 respondents. The analysis uses Structural Equation Modeling testing through SmartPLS. The results showed that motivation has a role in mediating the relationship between organizational culture and employee commitment to school administration staff' career development in South Tangerang Region.